Determinants of Acute Respiratory Infection in Children Under Five in Simalingkar, Medan, North Sumatera - Lasma Maria; Maestro Simanjuntak; Thomas Silangit; Jekson Martiar Siahaan (Masters Program in Public Health, 2020)
Background: Acute Respiratory Infection (ARI) is still one of the health problems in developed and developing countries including Indonesia. ARI is the most common disease in outpatients in North Sumatra, especially in Medan. This study aims to find out about the factors that influence ARI in toddlers in Sima